Mexique, Amerique Central, Antilles - Dumas-Vorzet, Ed.; Erhard, Hachette
This map shows Central America and the Caribbean as well as the surrounding areas. Countries are shaded in color (corresponding to a key near the upper right corner) and the states of Mexico are outlined in green. Some major cities, bodies of water and geographic features are marked (with relief shown by hachures). There are four insets: the Isthmus of Panama (lower right corner), and the islands of St. Martin, La Martinique, and La Guadeloupe in the upper right corner. Scale [ca. 1:2,285,700].